PENGARUH AUDIT TENURE, OPINI AUDIT TAHUN SEBELUMNYA, DAN DISCLOSURE TERHADAP OPINI AUDIT GOING CONCERN - Mohammad Nur Fahmi (Department of Accounting-Faculty of Economic and Business (FEB), 2015)
The purpose of this research is proving the effect of audit tenure, prior year auditopinion, and disclosure to going concern audit opinion. This research uses samples of miningand agriculture companies that listed at Indonesian Stock Exchange in 2011-2014. Based onpurposive sampling method, total of samples of this research are 56 companies. Thehypothesis in this research uses logistic regression. This research shows that prior year auditopinion has significant effect on the going concern audit opinion. Audit tenure and disclosuredo not have significant effect on the going concern audit opinionDOI: 10.15408/akt.v8i3.2770